A Differential Theory of Cinematic Affect. Issue 4 (November 2021) - Åkervall, Lisa
Abstract : This essay offers a critical rejoinder to affect theories prevalent in the humanities since the 1990s. In film and media studies, affect theories display an opposition to 'screen' and apparatus theory of the 1970s and 1980s alleged to have marginalised the spectator's body and affects and privileged cognition over affection. Yet film and media studies' turn to affect came with its own set of problems: in emphasising the affective over the cognitive aspects of cinematic experience, theories of the affective turn invert and reproduce the dichotomies (e.g. body/mind, affect/thought) they seek to contest. Critically reconsidering the turn to affect and its place within film and media studies, this article challenges the relation of affect theories to Gilles Deleuze's concept of affect, highlighting these theories' failure to account for Deleuze's indebtedness to Immanuel Kant's aesthetics and his theory of the faculties. Suggesting a conception of cinematic affect beyond dichotomies of body and mind, affect and thought, this essay instead shows how cinematic experience instigates transformations in spectators that are simultaneously affective and cognitive.